Risk and reliability in ground engineering proceedings of the conference organised by the Institution of Civil Engineers, and held in London on 11 and 12 November 1993 - Skipp, B. O. (Thomas Telford, 1994)
Includes studies on understanding, recognizing, evaluating and managing risk and these issues are discussed both in theory and in practice. This book examines the design issues affecting risk, and compares the types of ground conditions and their relative risks, through case histories. It is designed for anyone involved in ground engineering.